A comparative analysis on multiple intelligences between science technology and social sciences students at Universiti Teknologi MARA / Nor Fuzaina Ismail...[et al.] - Ismail, Nor Fuzaina; Jahya, Arnida; Hashim, Hadzli; Zulkiflf, Faiz; Ahmad Ridzuan, Ahmad Nur Azam; Abu Bakar, Norida; Md Jelas, Imran (2014)
This paper describes the comparison of multiple intelligence indexes between science technology students and social science students at Universiti Teknologi MARA. The multiple intelligence indexes were based on Howard Gardner's MI Model and Walter Mackenzie's Questionnaires. It was found that science social students attained higher MI index as compared to science technology students. The multiple intelligence profiling represents a significant departure from the traditional view of intelligence between these two groups. It is hoped that the indexes could offer a key consideration to match the learning strategies approaches by giving some insights about students' strength and weakness.